2023
DOI: 10.1093/europace/euad143
|View full text |Cite
|
Sign up to set email alerts
|

Risk of myocardial infarction and ischemic stroke in individuals with first-diagnosed paroxysmal vs. non-paroxysmal atrial fibrillation under anticoagulation

Abstract: Aims There is conflicting evidence on whether the type of atrial fibrillation (AF) is associated with risk of cardiovascular events, including acute myocardial infarction (MI) and ischemic stroke. The aim of the present study was to investigate whether the risk of MI and ischemic stroke differs between individuals with first-diagnosed paroxysmal vs. non-paroxysmal AF treated with anticoagulants. Methods and results De-identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Multivariate regression analysis showed that the AHRE≥48 h could predict the stroke well ( p = .001). Similar result was found in a current propensity‐matched cohort study, and no significant association was observed between the type of AF and risk of ischemic stroke (HR: 1.09, 95%CI: 0.95–1.25) 26 . Should we modify the anticoagulant strategies based on AHRE? 27,28 More investigations is necessary in the future clinical trials.…”
Section: Discussionsupporting
confidence: 62%
“…Multivariate regression analysis showed that the AHRE≥48 h could predict the stroke well ( p = .001). Similar result was found in a current propensity‐matched cohort study, and no significant association was observed between the type of AF and risk of ischemic stroke (HR: 1.09, 95%CI: 0.95–1.25) 26 . Should we modify the anticoagulant strategies based on AHRE? 27,28 More investigations is necessary in the future clinical trials.…”
Section: Discussionsupporting
confidence: 62%
“…The research on the TriNetX online research platform was performed on 26 November 2022 for patients aged ≥18 years with AF or flutter (ICD-10-CM code I48). As previously described, 17 the baseline index event was the first AF diagnosis reported into the TriNetX platform. Any medical diagnosis and cardiovascular procedures or treatment registered into the system within 5 years from the index event were considered as an individual baseline characteristic.…”
Section: Methodsmentioning
confidence: 99%
“…As its incidence and prevalence increase with age, it is estimated that about 17.9 million adults aged over 55 years in 2060 will experience AF in the European Union ( 3 ). Adjusting for age and predisposing conditions, AF has been associated with an increased risk of stroke ( 4 ), heart failure ( 5 ), myocardial infarction (MI) ( 6 ) and death ( 7 , 8 ). In addition, numerous previous studies, including several meta-analyses, provide growing evidence of an association between AF and cognitive decline in the absence of clinically overt previous stroke ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%